Charlie the ranch dog - Drummond, Ree.; De Groat, Diane (New York : Harper, 2011)
While Charlie, a sleepy basset hound, tells about the busy life of a ranch dog, his best friend Suzie, a Jack Russell terrier, is getting the work done.
Ages 4-8.
Keywords: Ranch life -- Fiction; Basset hound -- Fiction; Jack Russell terrier -- Fiction; Dogs -- Fiction